Effect of Fiscal Decentralization on District/City Community Welfare in South Sulawesi Province - Satrio Angga Murti (Institute of Computer Science (IOCS), 2022)
This study aims to see the effect of fiscal decentralization and capital spending on people's welfare both directly and indirectly through economic growth. Researchers used panel data from 24 districts/cities in South Sulawesi Province for the 2016-2021 period. The model used is panel data regression assisted by the E-views 12 application. The results of this study indicate that fiscal decentralization has no significant effect on economic growth. Capital expenditure has a significant effect on economic growth. Fiscal decentralization, capital expenditure and economic growth have a significant effect on people's welfare. Fiscal decentralization on people's welfare through economic growth has no significant effect, Capital expenditure on people's welfare through economic growth has a significant effect.